1982
DOI: 10.1161/01.cir.65.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of experimental infarct size by an angiotensin-converting enzyme inhibitor.

Abstract: SUMMARY The effects of angiotensin-converting enzyme inhibitor (CEI) SQ14225 on infarct size and regional myocardial blood flow were studied in 21 anesthetized dogs subjected to 6 hours of coronary occlusion. An area of myocardium at risk of necrosis was determined in vivo after 15 minutes of coronary occlusion but before CEI treatment (AR1) using an autoradiographic technique and after treatment after 6 hours of coronary occlusion (AR2) using a fluorescent dye technique. An MYOCARDIAL ISCHEMIA and, ultimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
77
1
7

Year Published

1988
1988
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(94 citation statements)
references
References 39 publications
9
77
1
7
Order By: Relevance
“…In this respect, our results are in agreement with those of other studies performed with ACEIs (Liang et al, 1982;Daniell et al, 1984;De Lorgeril et al, 1992). In contrast, other investigators have reported an increase in regional myocardial blood flows and a limitation of infarct size with captopril in dogs (Ertl et al, 1982). However, several experiments suggest that the anti-ischaemic effect of the sulphydryl-containing ACEI captopril could be due to non specific effects of this drug, such as an inhibition of oxygen free radical-dependent reperfusion injury (Westlin & Mullane, 1988;Chopra et al, 1992) and/or an interference with arachidonic acid metabolism (Van Gilst et al, 1987).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In this respect, our results are in agreement with those of other studies performed with ACEIs (Liang et al, 1982;Daniell et al, 1984;De Lorgeril et al, 1992). In contrast, other investigators have reported an increase in regional myocardial blood flows and a limitation of infarct size with captopril in dogs (Ertl et al, 1982). However, several experiments suggest that the anti-ischaemic effect of the sulphydryl-containing ACEI captopril could be due to non specific effects of this drug, such as an inhibition of oxygen free radical-dependent reperfusion injury (Westlin & Mullane, 1988;Chopra et al, 1992) and/or an interference with arachidonic acid metabolism (Van Gilst et al, 1987).…”
supporting
confidence: 93%
“…It has been shown that blockade of the renin-angiotensin system by captopril (Ertl et al, 1982), enalapril (Lefer & Peck, 1984;Hock et al, 1985), and ramipril (Martorana et al, 1990) produces a beneficial effect in myocardial ischaemia. However, this cardioprotective effect of angiotensin Iconverting enzyme inhibitors (ACEIs) is not universally recognized, as Liang et al (1982) and Daniell et al (1984) have failed to demonstrate any myocardial protection with ACEIs.…”
Section: Introductionmentioning
confidence: 99%
“…For C K and CK-MB determinations, blood samples were taken hourly for the first 6 h, and thereafter every 6 h for 48 h and beyond (assay: Merck, Darmstadt). Three patients in the placebo group required cardioversion for ventricular fibrillation; in two patients, this procedure was required more than once, and in these only CK-MB was taken into account.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…37 Some experimental studies reported that ACE inhibition in the immediate post-MI period could reduce both infarct size 38 and myocardial damage. 39 However, our own experiments failed to demonstrate a reduction of infarct size, 40 and a subsequent large clinical trial indicated that ACE inhibition given intravenously immediately after MI was not beneficial.…”
Section: Angiotensin Ii-mediated Effectsmentioning
confidence: 99%